Evaluation of Breast Lump by Fine Needle Aspiration Cytology - Poudel, Suman; Ranabhat, S; Parajuli, B; Pun, G (Journal of Gandaki Medical College-Nepal, 2017)
Introduction: Fine needle aspiration cytology (FNAC) is the important part of triple assessment in diagnosing the palpable breast lump. It categorizes the lesion into benign, malignant and its subtypes. It can also identify the residual diseases after treatment. Methods: It was a cross sectional descriptive study of cases of breast lump carried out during June 2015 to May 2016 in the Department of Pathology, Gandaki Medical College Teaching Hospital, Pokhara, Nepal. All the patients presenting in Pathology Department with history of breast lump were examined in detail. FNAC was done by standard procedure; smears were prepared and stained with Giemsa and pap for evaluation. Histopathology slides were stained with hematoxylin and eosin stain and evaluated by pathologists in Gandaki Medical College Teaching Hospital. Results: The study showed that, fibroadenoma of breast is the commonest benign lesion among the young populations. Only 13.11% of breast lump is malignant in the elderly population. Conclusion: FNAC is one of the safest and cheapest procedure that can be done in outpatient department for the diagnosis of breast lump. And there is no significant difference in diagnosis made by FNAC and histopatholgy examination. Journal of Gandaki Medical College Volume, 09, Number 2, July December 2016, Page: 38-42